Handbook of offshore helicopter transport safety : essentials of underwater egress and survival - Taber, Michael J. (Woodhead Publishing in mechanical engineering., 2016)
Handbook of Offshore Helicopter Transport Safety: Essentials of Underwater Egress and Survival provides a comprehensive look at the issues and concerns facing offshore helicopter transport. The book offers guidance for offshore helicopter operators, survival instructors, and the global offshore workforce, including discussions of safety management systems, safety briefings, survival equipment, underwater egress training, water impact/ditching statistics, and search and rescue. Each area of interest details pertinent information spanning approximately 30 years of offshore operations. Early sections discuss helicopter transport safety, safety regulations, and standards, while subsequent chapters cover Helicopter Underwater Escape Training (HUET) programs and their development and training, followed by final chapters on the effects of HUET, Emergency Breathing Systems (EBS), and Helicopter Transportation Suit (HTS).